Disruption of Cholesterol 7α-Hydroxylase Gene in Mice: II. BILE ACID DEFICIENCY IS OVERCOME BY INDUCTION OF OXYSTEROL 7α-HYDROXYLASE - Schwarz, Margrit (J Biol Chem, 1996)
Past experiments and current paradigms of cholesterol homeostasis suggest that cholesterol 7α-hydroxylase plays a crucial role in sterol metabolism by controlling the conversion of cholesterol into bile acids. Consistent with this conclusion, we show in the accompanying paper that mice deficient in cholesterol 7α-hydroxylase (Cyp7(−/−) mice) exhibit a complex phenotype consisting of abnormal lipid excretion, skin pathologies, and behavioral irregularities (Ishibashi, S., Schwarz, M., Frykman, P. K., Herz, J., and Russell, D. W. (1996) J. Biol. Chem. 261, 18017–18023). Aspects of lipid metabolism in the Cyp7(−/−) mice are characterized here to deduce the physiological basis of this phenotype. Serum lipid, cholesterol, and lipoprotein contents are indistinguishable between wild-type and Cyp7(−/−) mice. Vitamin D(3) and E levels are low to undetectable in knockout animals. Stool fat content is significantly elevated in newborn Cyp7(−/−) mice and gradually declines to wild-type levels at 28 days of age. Several species of 7α-hydroxylated bile acids are detected in the bile and stool of adult Cyp7(−/−) animals. A hepatic oxysterol 7α-hydroxylase enzyme activity that may account for the 7α-hydroxylated bile acids is induced between days 21 and 30 in both wild-type and deficient mice. An anomalous oily coat in the Cyp7(−/−) animals is due to the presence of excess monoglyceride esters in the fur. These data show that 7α-hydroxylase and the pathway of bile acid synthesis initiated by this enzyme are essential for proper absorption of dietary lipids and fat-soluble vitamins in newborn mice, but not for the maintenance of serum cholesterol and lipid levels. In older animals, an alternate pathway of bile acid synthesis involving an inducible oxysterol 7α-hydroxylase plays a crucial role in lipid and bile acid metabolism.